The MBRAS book of over 1,600 Malay proverbs - Sheppard, Mubin (Monographs of the Malaysian Branch, Royal Asiatic Society, 1992)
The Malay proverbs which have been assembled in this book contains many reference to the forests, the plants, the birds, animals and fishes - some friendly, many natural enemies, a vivid array of the villager's company.